Outcomes for Gestational Carriers Versus Traditional Surrogates in the United States - Fuchs, Erika L. (J Womens Health (Larchmt), 2018)
Background: Little is known about the obstetric and procedural outcomes of traditional surrogates and gestational carriers. Materials and Methods: Participants included 222 women living in the United States who completed a brief online survey between November 2015 and February 2016. Differences between gestational carriers (n = 204) and traditional surrogates (n = 18) in demographic characteristics, pregnancy outcomes, and procedural outcomes were examined using chi-squared tests, Fisher's exact tests, and t-tests. Results: Out of 248 eligible respondents, 222 surveys were complete, for a response rate of 89.5%. Overall, obstetric outcomes were similar among gestational carriers and traditional surrogates. Traditional surrogates were more likely than gestational carriers to have a Center for Epidemiologic Studies Depression Scale Revised score of 16 or higher (37.5% vs. 4.0%). Gestational carriers reported higher mean compensation ($27,162.80 vs. $17,070.07) and were more likely to travel over 400 miles (46.0% vs. 0.0%) than traditional surrogates. Conclusions: Procedural differences, but not differences in obstetric outcomes, emerged between gestational carriers and traditional surrogates. To ensure that both traditional surrogates and gestational carriers receive optimal medical care, it may be necessary to extend practice guidelines to ensure that traditional surrogates are offered the same level of care offered to gestational carriers.